PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VII.1 SMP NEGERI 1 KAMPAR TIMUR - Khairani, Elvia; Roza, Yenita; Siregar, Syarifah Nur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is classroom action research that aims to improve learning process and to increase student mathematics achievement with applied the learning model of Problem Based Learning. The subject of this research are student of class VII.1 SMP Negeri 1 Kampar Timur in academic years 2017/2018, which are 29 students, consist of 15 boys and 14 girls. The research consist of two cycles, each cycle has four stages, which are planning, implementation, observation, and reflection. The instruments of data collection in this research is the observation sheets and students mathematic tests. The observation sheets were analyzed in qualitative desciptive, while the students mathematic tests were analyzed in quantitative descriptive. The qualitative descriptive showed an improvement of learning process prior to the action on the first and second cycle. Most of students were very confidenced and actived in learning process. The results of this study indicate the number of students who reached Minimum Mastery Criteria of knowledge increase from basic score to UH-I and UH-II. The results of this research showed an increasing number of students learning mathematics about knowledge of the basic score (24,14%) to the first UH-I (48,24%) to the UH-II (79,31%) thus it can be concluded that the application of Problem Based Learning (PBL) model can improve learning process and increase mathematics achievement from the students at class VII.1 SMP Negeri 1 Kampar Timur in academic years 2017/2018 for the sets.Key Words: Students’ Mathematic Achievement, Problem Based Learning, Class Action Research